Etchant for displaying color metallographic structure of high manganese steel used at low temperature and use method of etchant

By using an etching agent composed of sulfuric acid and sodium sulfite, combined with the principle of thin film interference phenomenon, the problem of unclear display of the metallographic structure of high manganese steel in the existing technology has been solved, and the clear, accurate and fine display of the color metallographic structure has been achieved, and the Rich organizational information.

CN119310076APending Publication Date: 2025-01-14CHINA SHIPBUILDING INDUSTRY CORPORATION NO725 RESEARCH INSTITUTE +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411445907.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The erosive agent used in the prior art to display the metallographic structure of high manganese steel cannot clearly, accurately and precisely display the color metallographic structure of high manganese steel for low temperatures, resulting in insufficient austenite grain contrast and general color contrast. and organizational characterization information is small.

Method used

Using an etchant containing sulfuric acid and sodium sulfite, a thin film is produced on the test surface of the sample through specific chemical dyeing reagent technology, and the thin film interference phenomenon is used to present colorful tissue images under an optical microscope.

Benefits of technology

It achieves clear, accurate and fine display of austenite colored grains of high manganese steel with good color contrast, and can obtain fine structural information such as the relative orientation of grains, stress state, and microscopic deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119310076A_ABST
    Figure CN119310076A_ABST
Patent Text Reader

Abstract

The invention discloses an aggressive agent for displaying a color metallographic structure of high manganese steel used at low temperature and a use method, and the aggressive agent comprises sulfuric acid and sodium sulfite; the ratio of the aggressive agent is as follows: every 100 mL of deionized water contains 5-15 mL of sulfuric acid and 3-8 g of sodium sulfite. The use method comprises the following steps: S1, preparing a sample; s2, preparing an aggressive agent, and standing the prepared aggressive agent for a period of time; s3, eroding the sample; s4, washing the sample; and S5, carrying out metallographic observation, and taking a metallographic picture. According to the aggressive agent and the use method, a thin film with a certain thickness is prepared on a test sample inspection surface mainly through a specific chemical staining reagent technology, and a tissue image with a certain color is finally presented under an optical microscope by utilizing the principle of a thin film interference phenomenon; meanwhile, the microscope adopts an orthogonal polarization and color sensitive wave plate mode, so that the film interference effect is more obvious, and the obtained color picture is richer in color and better in contrast.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallographic inspection of metal materials, in particular to an etchant for displaying the colored metallographic structure of low-temperature high-manganese steel and a use method thereof. Background Art

[0002] The mass fraction of the main alloying elements of high manganese steel for low temperature is: C: 0.4% ~ 0.6%, Mn: 22% ~ 26%, Cr: 3.0% ~ 4.0%. Compared with the traditional Ni-based low temperature steel, high manganese steel has the advantages of low material cost and excellent ultra-low temperature performance, and is mainly used in the manufacture of liquefied natural gas ships and storage tanks. The metallographic structure of high manganese steel at room temperature is twin austenite, and austenite still has considerable stability even under ultra-low temperature conditions (-163°C). The grain size and morphology of austenite have a significant effect on the static strength, plastic toughness and fatigue strength of high manganese steel. Therefore, a clear and complete display of the metallographic structure of high manganese steel for low temperature is helpful to control the processing and heat treatment process, and also provides an important technical basis for product quality inspection and verification of delivery.

[0003] At present, the etching agents and methods used to display the metallographic structure of high manganese steel mainly include: (1) 4% nitric acid alcohol etching; (2) 2-5% nitric acid aqueous solution etching, followed by wiping the surface oxide film with 5-7% oxalic acid alcohol solution; (3) 10-15% nitric acid alcohol solution etching, followed by wiping the surface oxide film with a mixed solution of hydrochloric acid, propylene glycol and alcohol. All three reagents can only display the metallographic structure of black and white contrast, and the austenite grain contrast is insufficient, which is not conducive to grain size rating and recrystallization determination.

[0004] Invention patent CN116121756A uses mixed reagents: 0.4-0.5g oxalic acid, 0.7-0.8g sodium metabisulfite, 4-4.5ml nitric acid, 98-102ml anhydrous ethanol to erode the sample. The configured etchant is only suitable for wear-resistant high manganese steel with a Mn mass fraction of 11% to 14%, and the color contrast is general, which is not conducive to obtaining information on the relative orientation of grains and microscopic deformation within the grains, and the amount of organizational characterization information is small. The color metallographic structure display method of high manganese steel for low temperature is still in a blank state. Summary of the invention

[0005] In view of this, the present invention aims to propose an etchant and a method of use for displaying the colored metallographic structure of high manganese steel for low temperature, which can clearly, accurately and finely display the colored metallographic structure of high manganese steel for low temperature, so as to solve the problems of insufficient austenite grain contrast, general color contrast and less information on organizational characterization in the prior art.

[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] The invention discloses an etchant for displaying the colored metallographic structure of high manganese steel for low temperature use, wherein the etchant comprises sulfuric acid and sodium sulfite; the specific proportion of the etchant is as follows: 5 to 15 mL of sulfuric acid and 3 to 8 g of sodium sulfite are contained in every 100 mL of deionized water.

[0008] Furthermore, the etching agent preparation process is as follows: sulfuric acid is slowly added into deionized water, and then sodium sulfite is immediately added, and the mixture is continuously stirred until uniform.

[0009] Furthermore, the mass fraction of the sulfuric acid is 95% to 98%.

[0010] A method for using an etchant for displaying the colored metallographic structure of low-temperature high-manganese steel comprises the following steps:

[0011] S1: Sample preparation: grinding and polishing the inspection surface of the metallographic sample to a mirror surface;

[0012] S2: Prepare the etchant and let it stand for a while;

[0013] S3: Etching the sample, immersing the inspection surface of the prepared metallographic sample into the etchant, with the inspection surface of the sample facing upwards, gently shaking the sample and leaving it for a while until a layer of oxide film is evenly coated on the inspection surface of the sample, and then taking out the sample;

[0014] S4: Rinse the sample. Immediately rinse the sample with deionized water, then rinse with anhydrous ethanol, and blow dry the test surface.

[0015] S5: Conduct metallographic observation, take metallographic photos, adjust the polarization angle of the optical microscope to obtain a state with good color contrast on the sample inspection surface, observe the sample inspection surface after corrosion, and take metallographic structure photos.

[0016] Furthermore, the specific operations of grinding and polishing in step S1 are: the test surface of the sample is grinded step by step from coarse to fine with water sandpaper, and then polished with flannel cloth and diamond polishing agent.

[0017] Furthermore, the particle size of the diamond polishing agent is 0.5 μm.

[0018] Furthermore, the standing time of the etching agent in step S2 is 30 to 60 seconds; and the residence time of immersing in the etching agent in step S3 is 2 to 10 seconds.

[0019] Furthermore, the mode of the optical microscope in step S5 is an orthogonal polarization mode, and a color-sensitive wave plate is inserted.

[0020] Furthermore, the metallographic structure photograph is a color metallographic structure photograph.

[0021] Furthermore, the mass fraction of Mn in the high manganese steel for low temperature use is 22% to 26%.

[0022] Compared with the prior art, the etchant and use method for displaying the colored metallographic structure of low-temperature high-manganese steel described in the present invention have the following advantages:

[0023] (1) The present invention mainly uses a specific chemical dyeing reagent technology to prepare a film of a certain thickness on the test surface of the sample, and uses the principle of thin film interference phenomenon to finally present a colorful tissue image under an optical microscope; at the same time, the microscope adopts the mode of orthogonal polarization + color-sensitive wave plate, and the thin film interference effect is more significant, and the obtained color photos are more colorful and have better contrast. Compared with ordinary black and white metallographic photos, the present invention can clearly, accurately and finely display the colored grains of high manganese steel austenite with good color contrast, and can also obtain fine tissue information such as relative orientation of grains, stress state, and microscopic deformation.

[0024] (2) The present invention utilizes the easy oxidation property of high manganese steel, selects oxidizing acid to prepare an etchant of a specific concentration, and uses an etching method to perform oxidation film formation. The main components of the etchant are sulfuric acid and sodium sulfite, which can work together to achieve reasonable regulation of the pH value and oxidizing property of the etchant. The etchant is simple to prepare, and the etching method is easy to operate and safe. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0026] Figure 1 This is the metallographic morphology of the sample in Example 1;

[0027] Figure 2 This is the metallographic morphology of the sample in Example 2;

[0028] Figure 3 This is the metallographic morphology of the sample in Example 3;

[0029] Figure 4 This is the metallographic morphology of the sample of Example 4;

[0030] Figure 5 This is the metallographic morphology of the sample in Example 5;

[0031] Figure 6 This is the metallographic morphology of the sample in Example 6;

[0032] Figure 7 This is the metallographic morphology of the sample of comparative example 1;

[0033] Figure 8 This is the metallographic morphology of the sample in comparative example 2;

[0034] Fig. 9 This is the metallographic morphology of the sample of comparative example 3;

[0035] Fig.10 This is the metallographic morphology of the sample of comparative example 4;

[0036] Fig.11 This is the metallographic morphology of the sample in comparative example 5;

[0037] Fig.12 This is the metallographic morphology of the sample of comparative example 6;

[0038] Fig.13 This is the metallographic morphology of the sample of comparative example 7;

[0039] Fig.14 This is the metallographic morphology of the sample in comparative example 8. DETAILED DESCRIPTION

[0040] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.

[0041] The present invention provides a method for using an etchant for displaying the colored metallographic structure of low-temperature high-manganese steel, which specifically comprises the following steps:

[0042] S1: Sample preparation: grinding and polishing the inspection surface of the metallographic sample to a mirror surface.

[0043] Specifically, the metallographic specimens in this application all refer to high manganese steel for low temperature. The inspection surface of the metallographic specimen is polished step by step from coarse to fine with water sandpaper. Specifically, it is polished with 80 mesh, 240 mesh, 400 mesh, and 800 mesh water sandpaper. The polished metallographic specimen is polished with flannel cloth + 0.5μm diamond polishing agent, and the inspection surface of the specimen is free of pollution and mirror-like state without the influence of original processing.

[0044] S2: Prepare an etchant. The specific formula of the etchant used in the present invention is: 5-15 mL of sulfuric acid, 3-8 g of sodium sulfite and 100 mL of deionized water; the preparation process of the above-mentioned etchant is: slowly add sulfuric acid to deionized water, and then immediately add sodium sulfite, and continue stirring until uniform.

[0045] Taking advantage of the easy oxidation of high manganese steel and the fact that the electrolysis capacity of sulfuric acid in aqueous solution is greater than that of nitric acid in anhydrous ethanol, an oxidizing acid is selected: sulfuric acid is used to prepare an etching solution of appropriate concentration to etch the high manganese steel. At the same time, sodium sulfite is quickly added to the sulfuric acid solution and stirred evenly. At this time, sulfuric acid and sodium sulfite will undergo a double decomposition reaction, which can quickly form a film layer on the surface of the high manganese steel, greatly reducing the corrosion waiting time;

[0046] Specifically, sulfuric acid and sodium sulfite undergo the following chemical reaction:

[0047] 2Na2SO3+H2SO4(a small amount)=Na2SO4+2NaHSO3;

[0048] Na2SO3+H2SO4(excess)=Na2SO4+H2O+SO2↑.

[0049] When the amount of sulfuric acid is small, after adding sodium sulfite, the reaction generates weakly acidic sodium bisulfite, which, together with sulfuric acid, corrodes the high manganese steel to prevent the corrosion liquid from being weak in oxidation and acidity, and unable to generate an oxide film layer that is completely and evenly coated on the surface of the metallographic sample.

[0050] When the amount of sulfuric acid is large, after adding sodium sulfite, the reaction generates sulfate soluble in water, which reduces the acidity and oxidizing properties of sulfuric acid, prevents the oxidizing property and acidity in the etching solution from being too strong, causing the metallographic specimen to be over-corroded, the precipitated phase at the grain boundary / intragranular phase to fall off, etc., resulting in mottled metallographic surface affecting the subsequent color metallographic structure shooting.

[0051] In summary, the selection of sulfuric acid, sodium sulfite and deionized water to prepare the etching solution can achieve reasonable regulation of the pH value and oxidizing properties of the etching agent, so that a film layer can be quickly formed on the surface of high manganese steel, greatly reducing the corrosion waiting time; at the same time, it can also prevent the occurrence of mottled metallographic surface or uneven film layer caused by excessive or weak oxidizing properties of the etching solution.

[0052] S3: Etch the sample. After the prepared etchant is left to stand for 30 to 60 seconds, immerse the test surface of the prepared metallographic sample into the etchant with the test surface facing upward. Gently shake the sample and leave it for 2 to 10 seconds until the test surface of the sample is evenly covered with an oxide film, then take out the sample.

[0053] S4: Rinse the sample. Immediately rinse the sample with deionized water, then rinse with anhydrous ethanol, and blow dry the test surface.

[0054] In the corrosion process of existing high manganese steel, it is necessary to completely remove the film layer of the sample inspection surface when observing the metallographic structure. However, the present application utilizes the principle of thin film interference, and there is no need to remove the surface film layer of the sample inspection surface. The operation is simple, convenient and fast. Therefore, it also avoids the occurrence of over-corrosion of the inspection surface and the shedding of grain boundary / intragranular precipitation phases during the film removal process. Therefore, the sample inspection surface with clear grains and good color contrast can be observed under an optical microscope; clear and colorful metallographic structure images can also be taken; thereby obtaining fine structure information such as relative orientation of grains, stress state, and microscopic deformation.

[0055] S5: Conduct metallographic observation, take metallographic photos, adjust the polarization angle of the optical microscope to obtain a state with good color contrast on the sample inspection surface, observe the sample inspection surface after corrosion, and take metallographic structure photos.

[0056] Example 1

[0057] Take Mn24 hot-rolled state-1 plate as metallographic specimen, use sulfuric acid and sodium sulfite as etching agents, specifically:

[0058] S1: Sample preparation: After the sample is polished with 80 mesh, 240 mesh, 400 mesh, and 800 mesh water sandpaper, it is polished with flannel cloth and diamond polishing agent with a particle size of 0.5μm. The test surface of the sample is in a mirror-like state with no pollution and eliminating the original processing influence.

[0059] S2: Prepare the etchant by adding 10 mL of sulfuric acid (mass fraction 95% to 98%) to 100 mL of deionized water by volume, then immediately add 5 g of sodium sulfite, stir evenly, and let the prepared etchant stand for 40 seconds;

[0060] S3: Etch the sample. Immerse the test surface of the sample in the above-prepared etchant, with the test surface facing upwards. Gently shake the sample and leave it for 5 seconds until a layer of oxide film is evenly coated on the test surface of the sample. Then take out the sample.

[0061] S4: Rinse the sample. Immediately rinse the test surface of the sample with deionized water, then rinse with anhydrous ethanol, and blow dry the test surface;

[0062] S5: Perform metallographic observation, take metallographic photos, adjust the polarization angle of the optical microscope, specifically the orthogonal polarization and color-sensitive waveplate mode, obtain a state with good color contrast on the sample inspection surface, observe the sample inspection surface after corrosion, and take metallographic structure photos.

[0063] The results are shown as Figure 1 As shown, the twin austenite grain boundaries of the sample are clear and the color contrast is good; the material grains are small and uniform, indicating that the material has been completely recrystallized; since the grain color is mainly blue and brown, it shows that the sample has a certain degree of plate texture.

[0064] Example 2

[0065] The concentration of the etchant in Example 2 is different from that in Example 1, and the metallographic sample material, etchant standing time, etching time and microscope mode are the same as those in Example 1.

[0066] Example 2: Prepare the etchant: add 15 mL of sulfuric acid to 100 mL of deionized water, immediately add 8 g of sodium sulfite, and stir evenly; the other steps are the same as in Example 1;

[0067] The results are shown as Figure 2 As shown in the figure, the twin austenite grain boundaries of the sample are clear and the color contrast is good; the grains are small in most areas, and coarse grains exist locally, indicating that the plate is not completely recrystallized; in addition, deformation bands can be seen inside the coarse grains.

[0068] Example 3

[0069] The metallographic sample material, etchant concentration, etchant standing time and etchant time of Example 3 are different from those of Example 1, and the microscope mode is the same as that of Example 1.

[0070] Example 3: Mn24 hot-rolled state-2 plate is selected as the metallographic sample.

[0071] Prepare the etching agent: add 5 mL of sulfuric acid into 100 mL of deionized water, immediately add 3 g of sodium sulfite, and stir evenly; let the prepared etching agent stand for 60 seconds;

[0072] Immerse the inspection surface of the metallographic sample in the above-prepared etchant, with the inspection surface of the sample facing upwards, gently shake the sample and leave it for 10 seconds until a layer of oxide film is evenly coated on the inspection surface of the sample, then take out the sample;

[0073] The other steps are the same as those in Example 1.

[0074] The results are shown as Figure 3 As shown, the twin austenite grain boundaries of this sample are clear and the color contrast is good;

[0075] Example 4

[0076] The concentration of the etchant, the etchant standing time and the etchant time in Example 4 are different from those in Example 3, and the metallographic sample material and the microscope mode are the same as those in Example 3.

[0077] Example 4 Prepare an etchant: add 15 mL of sulfuric acid to 100 mL of deionized water, immediately add 8 g of sodium sulfite, and stir evenly; let the prepared etchant stand for 30 seconds;

[0078] Immerse the inspection surface of the metallographic sample in the above-prepared etchant, with the inspection surface of the sample facing upwards, gently shake the sample and leave it for 2 seconds until a layer of oxide film is evenly coated on the inspection surface of the sample, then take out the sample;

[0079] The other steps are the same as those in Example 3.

[0080] The results are shown as Figure 4 As shown, the twin austenite grain boundaries of the sample are clear and the contrast is good; the grains are small and uniform, indicating that the material has been completely recrystallized; since the grain color is blue and brown, it shows that the sample has a certain degree of plate texture.

[0081] Example 5

[0082] The material of the metallographic sample in Example 5 is different from that in Example 3, and the concentration of the other etchants, the etchant standing time, the etching time and the microscope mode are the same as those in Example 3.

[0083] In Example 5, Mn24 annealed plate is selected as the metallographic specimen; other steps are the same as those in Example 3.

[0084] The results are shown as Figure 5 As shown in the figure, the twin austenite grain boundaries of the sample are clear and the color contrast is good; there are coarse grains in some parts of the sample, indicating that the plate is not completely recrystallized; in addition, obvious deformation bands can be seen inside the coarse grains.

[0085] Example 6

[0086] The material of the metallographic sample in Example 6 is different from that in Example 4, and the concentration of the other etchants, the etchant standing time, the etching time and the microscope mode are the same as those in Example 4.

[0087] In Example 6, Mn24 annealed plate is selected as the metallographic specimen; other steps are the same as those in Example 4.

[0088] The results are shown as Figure 6 As shown, the color contrast of the twinned austenite grains in the sample is obvious, and it can be seen that the annealed microstructure texture is not significant.

[0089] Examples 1 to 6 show that sulfuric acid + sodium sulfite aqueous solution as an etchant can be applied to many process states of low-temperature high manganese steel, including hot-rolled state, annealed state, etc.; when the etchant concentration is in the range of 5 to 15 ml of sulfuric acid, 3 to 8 g of sodium sulfite, and 100 ml of deionized water volume fraction, the etchant placement time is 30 to 60 s, and the etching time is in the range of 2 to 10 s, the microscope mode is orthogonal polarization and the color-sensitive wave plate mode can show excellent effects of good color contrast and clear grain boundaries.

[0090] Comparative Example 1

[0091] The microscope mode of Comparative Example 1 is different from that of Example 1, and other metallographic sample materials, etchant concentration, etchant standing time and etchant duration are the same as those of Example 1;

[0092] Comparative Example 1 The bright field mode of an optical microscope was used to observe the structure of the metallographic sample.

[0093] The results are shown as Figure 7 As shown, the coating thickness is appropriate when the sample surface appears orange in bright field.

[0094] The types and concentrations of the etchants in Comparative Examples 2 to 4 are different from those in Example 1, while the metallographic sample material, etchant standing time, etching time and microscope mode are the same as those in Example 1.

[0095] Etching agent prepared in Comparative Example 2: Add 10 mL of nitric acid into 100 mL of deionized water and stir evenly;

[0096] Etching agent prepared in Comparative Example 3: Add 10 mL of sulfuric acid into 100 mL of deionized water and stir evenly;

[0097] Etching agent prepared in Comparative Example 4: 5 g of sodium sulfite was added to 100 mL of deionized water and stirred evenly;

[0098] The display result of comparative example 2 is as follows Figure 8 As shown, the microstructure grains of the metallographic specimen are visible, but the color effect is poor.

[0099] The display result of comparative example 3 is as follows Fig. 9 As shown, due to the passivation effect of the sulfuric acid solution, the metallographic sample structure cannot be revealed and no colored grains are visible.

[0100] The display result of comparative example 4 is as follows Fig.10 As shown, the Mn24 structure of the metallographic sample cannot be seen in the metallographic photograph. This is because the sodium sulfite aqueous solution is weakly alkaline and cannot produce an oxide film on the surface of the metallographic sample.

[0101] Comparative Examples 5-6

[0102] The etchant concentrations of Comparative Examples 5-6 are different from those of Example 1, and the rest of the metallographic sample materials, etchant standing time, etching time and microscope mode are the same as those of Example 1.

[0103] The concentration of the etchant configured in Comparative Example 5 is as follows: 3 mL of sulfuric acid is added to 100 mL of deionized water, and 3 g of sodium sulfite is immediately added and stirred evenly;

[0104] The concentration of the etchant configured in Comparative Example 6 is as follows: 17 mL of sulfuric acid is added to 100 mL of deionized water, and 10 g of sodium sulfite is immediately added and stirred evenly;

[0105] The display result of comparative example 5 is as follows Fig.11 As shown in the figure, the austenite grains of the sample are not obvious, and there are still very obvious polishing marks remaining.

[0106] The display results of Comparative Example 6 are as follows Fig.12 As shown, most areas of the sample cannot show colored structures due to passivation, and only a small amount of grains near the inclusion phase or the second phase are visible.

[0107] Comparative Examples 7 to 8

[0108] The etchant standing time and etching time of Comparative Examples 7-8 are different from those of Example 1, and the rest of the metallographic sample materials, etchant concentrations and microscope modes are the same as those of Example 1.

[0109] Comparative Example 7: Let the prepared etching solution stand for 20 seconds, immerse the inspection surface of the metallographic sample in the prepared etching agent, with the inspection surface of the sample facing upward, gently shake the sample and leave it for 1 second until a layer of oxide film is evenly coated on the inspection surface of the sample, and then take out the sample;

[0110] Comparative Example 8: The prepared etching solution was allowed to stand for 80 seconds, and the inspection surface of the metallographic sample was immersed in the prepared etching agent, with the inspection surface of the sample facing upward, and the sample was gently shaken and left for 15 seconds until a layer of oxide film was evenly coated on the inspection surface of the sample, and the sample was taken out;

[0111] The display result of comparative example 7 is as follows Fig.13 As shown, the sample structure has insufficient color contrast, unclear grain boundaries, and no good color structure is obtained.

[0112] The display result of comparative example 8 is as follows Fig.14 As shown, the color contrast of the sample tissue is still insufficient and a good color tissue is not obtained.

[0113] Table 1 Processing parameters and experimental results of metallographic samples of comparative examples 1 to 7

[0114]

[0115]

[0116] According to Comparative Example 1, the microscope was in bright field mode, and metallographic tissue photographs were taken. The observed metallographic sample tissue coating thickness was appropriate, but there was no color contrast. At the same time, compared with Example 1, it was shown that under the same experimental conditions, a color tissue with obvious contrast, rich colors and clear boundaries could be obtained under polarized light.

[0117] According to Comparative Examples 2 to 4, when the type of the etchant is changed, that is, only a single nitric acid aqueous solution is used as the etchant, although the obtained colored metallographic structure grains are somewhat visible, the color effect of the metallographic structure photograph is poor, and when only a single sulfuric acid aqueous solution or a sodium sulfite aqueous solution is used as the etchant, the obtained colored metallographic structure grains are not visible; at the same time, compared with Example 1, it is shown that under the same experimental conditions, the sulfuric acid and sodium sulfite contained in the etchant of the present invention have a synergistic effect, and the pH and oxidizability of the etchant can be reasonably regulated, so that a complete and evenly coated oxide film layer can be quickly formed on the surface of the high manganese steel, and the obtained metallographic sample has clear grain boundaries and the color contrast of the structure photograph is good.

[0118] According to Comparative Examples 5 to 6, when the concentrations of sulfuric acid and sodium sulfite aqueous solutions in the etchant are too low or too high, the obtained color metallographic structure photographs are not ideal. When the concentration of the etchant is low, the corrosiveness and oxidizing properties are insufficient, resulting in unclear austenite grains and very obvious polishing marks remaining. When the concentration of the etchant aqueous solution is high, due to the passivation effect, only part of the sample or even no colored grains are visible.

[0119] According to Comparative Examples 7 to 8, when the etching agent standing time and etching time are short, the sample tissue is prone to problems of insufficient corrosiveness and oxidizability, and insufficient tissue color contrast; when the etching agent standing time and etching time are long, there will be an over-corrosion state caused by the passivation effect, which will reduce the tissue color contrast and blur the grain boundaries.

[0120] The invention utilizes the easy oxidation property of high manganese steel, selects oxidizing acid sulfuric acid to prepare an etchant of specific concentration, places the polished metallographic sample in the etchant for etching for a period of time, prepares a film of a certain thickness on the inspection surface of the sample by using a specific chemical dyeing reagent technology, and then places the sample under a microscope for observation, utilizes the principle of thin film interference phenomenon, and finally presents a colorful tissue image under an optical microscope; at the same time, under the mode of orthogonal polarization and color-sensitive wave plate of the microscope, the thin film interference effect is more significant, and the obtained color photo has richer colors and better contrast.

[0121] The above embodiments are only used to illustrate rather than limit the technical solutions of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An etchant for displaying the color metallographic structure of high manganese steel for low temperature use, characterized in that: The etching agent includes sulfuric acid and sodium sulfite; the specific ratio of the etching agent is: 5-15 mL sulfuric acid and 3-8 g sodium sulfite are contained in every 100 mL deionized water.

2. The etching agent according to claim 1, characterized in that The preparation process of the etching agent is as follows: sulfuric acid is slowly added into deionized water, and then sodium sulfite is immediately added, and the mixture is continuously stirred until uniform.

3. The etching agent according to claim 1, characterized in that The mass fraction of the sulfuric acid is 95% to 98%.

4. A method for using an etchant for displaying a colored metallographic structure of a low temperature high manganese steel, characterized in that: The following steps are involved: S1: Sample preparation: grinding and polishing the inspection surface of the metallographic sample to a mirror surface; S2: Prepare the etchant and let it stand for a while; S3: Etching the sample, immersing the inspection surface of the prepared metallographic sample into the etchant, with the inspection surface of the sample facing upwards, gently shaking the sample and leaving it for a while until a layer of oxide film is evenly coated on the inspection surface of the sample, and then taking out the sample; S4: Rinse the sample. Immediately rinse the sample with deionized water, then rinse with anhydrous ethanol, and blow dry the test surface. S5: Conduct metallographic observation, take metallographic photos, adjust the polarization angle of the optical microscope to obtain a state with good color contrast on the sample inspection surface, observe the sample inspection surface after corrosion, and take metallographic structure photos.

5. The method for using the etchant according to claim 4, characterized in that: The specific operation of grinding and polishing in step S1 is: the test surface of the sample is grinded step by step from coarse to fine with water sandpaper, and then polished with flannel cloth and diamond polishing agent.

6. The method for using the etchant according to claim 5, characterized in that: The particle size of the diamond polishing agent is 0.5 μm.

7. The method for using the etchant according to claim 4, characterized in that: The standing time of the etching agent in step S2 is 30 to 60 seconds; the residence time of immersing in the etching agent in step S3 is 2 to 10 seconds.

8. The method of use according to claim 4, characterized in that: The mode of the optical microscope in step S5 is the orthogonal polarization mode, and a color-sensitive wave plate is inserted.

9. The method of use according to claim 4, characterized in that: The metallographic structure photograph is a color metallographic structure photograph.

10. The method of use according to claim 4, characterized in that: The mass fraction of Mn in the low temperature high manganese steel is 22% to 26%.

Citation Information

Patent Citations

  • Etching agent and method for displaying color metallographic structure of wear-resistant high-manganese steel

    CN116121756A